PARTONUN'S POWER IN ULOS - Simbolon, Jupalman Welly; Purba, Dian; Sembiring, Feriel Amelia; Sihotang, Thrisia Yohana (Program Studi Sosiologi Universitas Malikussaleh, 2024)
This research aims to describe the power of partonun in ulos which has often been maintained by Uli, partonun ulos from Rura Silindung village, Tarutung. This type of research is descriptive qualitative with a phenomenological approach and literature study. Data collection was used by means of observation, in-depth interviews, documentation techniques from photographs. The results of the research show that the power of partonun ulos in the Rura Silindung area can only be exercised by those who can weave. Partonun ulos must have knowledge in designing and this knowledge is determined collectively because ulos is a representation of togetherness and will meet its end if it is collided with the need to pursue material things alone. Although this brings paralysis during industrial development in determining the design. However, this design must be maintained because it is part of remembering the historical route, creating, and controlling the work, and also loyalty to the ideal of balance between the partonun community and the environment.